Positional role and competitive-level differences in elite-level men's basketball players - Ben Abdelkrim, N.; Chaouachi, A.; Chamari, K.; Chtara, M.; Castagna, C. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the present study was to compare the physical attributes of elite men's basketball players according to age and specific individual positional roles. Forty-five players from 3 national basketball teams (Under-18 years, Under-20 years, and Senior) were measured for anthropometry (height, body mass, percentage body fat), explosive power (5 jumps and vertical jump), speed (5-m, 10-m, and 30-m sprint), agility (T-test), strength (bench press and squat 1 repetition maximum [1RM]), and intermittent high-intensity endurance performance (Yo-Yo intermittent recovery test [Yo-Yo IR1]). Data on match frequency, training routines, and playing experience were also collected. Under-18 players were significantly (p < 0.05) shorter and lighter than both Senior and Under-20 players but showed higher (p < 0.05) percentage body fat. Under-20 and Senior players were faster and had better explosive-power and agility (p < 0.05) performances than Under-18 players. Bench press and squat 1RMs were higher in Senior players (p < 0.05) compared with the other groups. There were significant difference in the Yo-Yo IR1 performance among groups (Senior > Under-20 > Under-18, p < 0.05). Centers and power forwards were the tallest and the heaviest (p < 0.05). The Yo-Yo IR1 performance was higher (p < 0.01) in point guards than in centers. Point guards showed also better agility and 5- and 10-m performances. Power forwards and centers were stronger than the rest of players' positions in the bench press 1RM (p < 0.01). These results showed the existence of age and positional role differences in fitness performance in men's basketball. Differences were particularly evident in intermittent high-intensity endurance and agility performance. Sprint training possibly should be individualized when dealing with positional roles in elite men's basketball. Strength and conditioning coaches should use Yo-Yo IR1 to assess specific endurance in players of different age and positional role.